Study of Wind Velocity Impact upon the Quality of Shielding and upon the Thermal Processes under MAG Welding - Chinakhov D. A. Dmitriy Anatol'evich; Vorobyev A. V. Aleksey Vasilievich; Grigoryeva E. G. Ekaterina Grigorievna; Mayorova E. I. (Metal Processing in Mechanical Engineering, 2015)
Title screen